ICU PATIENT MONITORING SYSTEM - J., S.Maria Nancy; J., Mohana (International Journal of Psychosocial Rehabilitation, 2020)
There is a strong need for integrated patient management services because they not only decrease manpower and expenses but also increase the time spent in professional facilities. Past wired networking has been used, but now the Zigbee wireless mesh network is preferred due to cost. Owing to its energy performance, low cost, and long range (several kilometres), Zigbee is often preferred for Bluetooth and wireless infrared communication. In this paper, we suggested the usage of the Zigbee interface to transmit wireless data between a patient and a centralized network The paper is split down into two parts. For certain cases, the first is a nurse management program and the second is a structured control device for doctors. Such two schemes, such as Zigbee, connect through wireless communication technologies. In a number of cases, we track the patient in the first segment. Several physiological parameters, such as individual patient’s ECG, temperature, and heart rate, were calculated by the respective instrument. When increasing physiological parameter value exceeds the threshold value, the warning signal and the LED will be activated for each patient device. This enables a doctor to interpret in real time the various physiological conditions in a case. The values for each unit of patients are seen on the LCD. Similarly, several patient-specific instruments are used to calculate certain clinical parameters, and a multi-patient tracking program is implemented. A unified patient monitoring method is implemented in the second portion, in which all parameters are shown using MATLAB for several parameters of central control. Using MATLAB tools, the ECG chart is shown on the main board. The main LCD shows parameters including heart rate and body heat, too. The module is cost-effective, uses low power and has reasonable range.